Modulation of amblyopia therapy following early surgery for unilateral congenital cataracts. - Lloyd, I C (1995)
BACKGROUND--Stimulus deprivation amblyopia is the principal cause of visual impairment in infants with unilateral congenital cataract. Even if lensectomy is undertaken at an early age, intensive postoperative occlusion of the phakic eye is essential for the development of useful vision in the aphakic eye. Despite this, the optimum method of regulating occlusion therapy is uncertain. METHODS--Interocular acuity differences identified using clinical preferential looking techniques (Keeler cards) were used to regulate target levels of phakic eye occlusion in a prospective evaluation of 10 systemically, metabolically, and neurologically normal infants in whom dense unilateral cataract was diagnosed before 8 weeks of age, and operated upon by 10 weeks. Actual occlusion levels were recorded each day by parents in a diary. The development of preferential looking acuity in the phakic and aphakic eye were compared with prediction intervals derived from observations on 43 normal children. RESULTS--Aphakic eye preferential looking acuities were within the normal range at last review in all but one infant. Interocular acuity differences were < or = 0.5 octave in all children older than 1 year of age at last review, and > or = 1 octave in three of four children less than 1 year old at last review (Fisher exact p = 0.033). Phakic eye acuities were within the normal range in all infants at all visits. CONCLUSION--Within the first 2 years of life, normal preferential looking acuity may be achieved in both eyes of infants undergoing early surgery for unilateral congenital cataract if occlusion therapy is modulated according to interocular acuity differences quantified by clinical preferential looking techniques.